Compact and tunable Erbium-Doped fiber laser with microfiber Mach–Zehnder interferometer - Sulaiman, A. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A compact and tunable Erbium-doped fiber laser is demonstrated using a highly concentrated Erbium-doped fiber in conjunction with a microfiber Mach–Zehnder interferometer (MMZI) structure for the first time. A stable laser output is achieved at 1531.7 nm region with a peak power of −19 dBm and an optical signal to noise ratio of 30.1 dB using a 980-nm pump at 100 mW power. The operating wavelength of the laser can be tuned from 1530.2 to 1532.7 nm by changing the path length difference (PLD) inside the MMZI from 1.6 to 2.7 mm at room temperature. It is also observed that the operating wavelength linearly shifts to a longer wavelength as the PLD increases with a tuning slope efficiency of 0.17 nm/mm. The tuning ability is due to the alteration of the induced optical phase shift inside the MMZI which affects the optical interference and the dominant peak which is responsible for the lasing action.